What happens to mood, performance and sleep in a laboratory study with no sleep deprivation?. Issue 3 (7th August 2013) - Paterson, Jessica L; Dorrian, Jill; Ferguson, Sally A; Jay, Sarah M; Dawson, Drew
Abstract: There are few studies examining changes in waking function in a laboratory environment with no sleep deprivation and mood has been largely overlooked in this context. The present study examined changes in mood, performance, sleep and sleepiness in the laboratory study with no sleep deprivation. Nineteen participants (10M, 9F; 22 ± 4.2 years) were given nine 9‐h sleep opportunities (23.00–08.00 hours). Every 2 h during wake, participants completed the Mood Scale II, a 10‐min Psychomotor Vigilance Task and measures of sleepiness and fatigue. Sleep was monitored using an electroencephalographic montage. Findings revealed significant negative mood change, performance impairment, reduced total sleep time and sleep efficiency (all P < 0.05). These findings suggest that the laboratory environment or procedural factors may impair mood, performance and sleep. These findings may have implications for interpreting impairments in mood, performance and sleep when observed in laboratory environments.